Impact of Awarding Insolvency of a Person on Consideration Transaction in Iranian Law - Alireza Fasihizadeh; Omid Hafizi; Mahmood Jalali; Morteza Tabibi (آموزه‌‌های فقه مدني)
There is no consensus among legal writers about the effect of bankruptcy of one party on the fate of the contract. Some consider it to be the reason for the annulment of the contract. The basis of this view is the collapse of a balance that should be between ability of delivery of each of the two considerations in all contracts. Most authors, however, have explained the provisions of Article 380 of the Civil Code and the seller’s discretion in the repayment of the object of the sale available to the buyer or the right of detaining in the case of a buyer’s bankruptcy based on his discretion in termination of the transaction that has been interpreted as the option for insolvency. A theory which, although it is to somehow adapted to some of the jurisprudential opinions and is referred to as one of the general rules of transactions, firstly, there was no explicit reference to it in civil law and in the interpretation of the Shiite jurisprudents it is often referred to as “right of returning”, not “option for insolvency”. Secondly, it is inconsistent with some of the relevant provisions of this law in the trade law. Thirdly, within the framework of the pure analyses of civil law, the supportive basis behind this article is more perfectly balanced with the maintaining the necessity of contract and, at the same time, taking into account the seller as a “creditor prior to other creditors”.